OPTIMIZATION OF PORTFOLIO PERFORMANCE ON THE JAKARTA ISLAM INDEX (JII) STOCK IN DECEMBER 2023 – MAY 204 USING THE MARKOWITZ MODEL - Rohman, Aletta Divna Valensia; Fatimah, Siti (iora, 2024)
This research aims to optimize the performance of a stock investment portfolio on the Jakarta Islamic Index (JII) during the period from December 2023 to May 2024, using the Markowitz model. This model minimizes portfolio risk by considering expected returns and covariance between stocks. Historical data on stock returns in the JII during the research period will be used to calculate expected returns and covariance. Furthermore, the Markowitz model will be used to determine the optimal investment proportion for each stock in the portfolio. The results of this research are expected to provide information to JII stock investors about the optimal combination of stocks to achieve maximum returns with controlled risk.